Detection and Quantitative Evaluation of Lupus Circulating Anticoagulant Activity - Rosner, Esther; Pauzner, Rachel; Lusky, Ayala; Modan, Michaela; Many, Amira (Thrombosis and Haemostasis, 1987)
Sixty-six SLE patients were studied for the presence of lupus type circulating anticoagulant. Forty-nine percent of them showed activity of this anticoagulant. The sensitivity of various coagulation tests was compared. Recalcification time was found to be the most sensitive screening test and the kaolin clotting time mixture test, the best for determining the presence of the anticoagulant.Tissue thromboplastin inhibition test detected only half of the patients in whom the anticoagulant was found by recalcification time and kaolin clotting time mixture test.APTT, using 2 different reagents, resulted in 73% and 52% false negatives. A numerical index for determining the presence of the anticoagulant and its quantitative evaluation is suggested.The association between thromboembolic events, recurrent abortions and the different coagulation tests is shown.
Keywords: Lupus type circulating anticoagulant; Numerical index ICA; Recalcification time